Evaluation of adjunctive mycophenolate for large vessel giant cell arteritis. Issue 2 (19th December 2020) - Karabayas, Maira; Dospinescu, Paula; Fluck, Nick; Kidder, Dana; Fordyce, Gillian; Hollick, Rosemary J; De Bari, Cosimo; Basu, Neil
Abstract: Objectives: GCA patients with large vessel involvement (LV-GCA) experience greater CS requirements and higher relapse rates compared with classical cranial GCA. Despite the distinct disease course, interventions in LV-GCA have yet to be investigated specifically. This study aimed to evaluate the CS-sparing effect and tolerability of first-line mycophenolate in LV-GCA. Methods: A retrospective cohort study was conducted in patients with LV-GCA identified from a regional clinical database between 2005 and 2019. All cases were prescribed mycophenolate derivatives (MYC; MMF or mycophenolic acid) at diagnosis and were followed up for ≥2 years. The primary outcome was the cumulative CS dose at 1 year. Secondary outcomes included MYC tolerance, relapse rates and CRP levels at 1 and 2 years. Results: A total of 37 patients (65% female; mean age 69.4 years, SD 7.9 years) were identified. All cases demonstrated large vessel involvement via CT/PET ( n = 34), CT angiography ( n = 5) or magnetic resonance angiography ( n = 2). After 2 years, 31 patients remained on MYC, whereas 6 had switched to MTX or tocilizumab owing to significant disease relapse. The mean (±SD) cumulative prednisolone dose at 1 year was 4960 (±1621) mg. Relapse rates at 1 and 2 years were 16.2 and 27%, respectively, and CRP levels at 1 and 2 years were 4 [interquartile range (IQR) 4–6] and 4 (IQR 4–4) mg/l, respectively. Conclusion: To our knowledge, this is the first attempt to assess the effectiveness of any specific agent in LV-GCA. MYC might be both effective in reducing CS exposure and well tolerated in this subpopulation. A future randomized controlled trial is warranted.